KAJIAN BIBLIKA TENTANG YESUS SEBAGAI PINTU DAN GEMBALA MENURUT YOHANES 10:1-18 - jonar Situmorang (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
This paper examines two things, which is Jesus' statement about Himself in the Gospel of John and a statement that begins with: